Detention and arrest - Coughlan, Steve (Essentials of Canadian Law, 2017)
The criminal justice system aims to maintain a balance between the individual interest of private citizens to carry on their lives free from state interference, and the communal interest in maintaining a safe society. These two goals come into conflict with each other most visibly when agents of the state physically take control of private citizens -- that is, when they exercise their powers to detain or to arrest.The book focuses on "street-level" encounters: detentions and arrests that occur in the course of investigating crime and laying charges. The authors explore the initial interaction between agents of the state or others authorized to detain and arrest, and the private citizens whose liberty is interfered with. It is at that point that the balance between societal safety and individual liberty is most keenly in play.This second edition has been updated to incorporate significant changes which have taken place with regard to statutory powers (the new citizen's arrest power and others), to common law powers (powers of detention, safety searches, search incident to arrest, etc.) and to Charter rights (freedom from arbitrary detention, right to counsel, and so on).